2020
DOI: 10.3389/fonc.2020.00049
|View full text |Cite
|
Sign up to set email alerts
|

Upregulated Expression of TUBA1C Predicts Poor Prognosis and Promotes Oncogenesis in Pancreatic Ductal Adenocarcinoma via Regulating the Cell Cycle

Abstract: Background: Pancreatic ductal adenocarcinoma (PDAC) is a highly malignant disease and has the worst prognosis and survival rate. TUBA1C is a microtubule component implicated in multiple cancers, however, the clinical significance and biological functions of TUBA1C in the progression of PDAC remain unexplored. Methods: The Cancer Genome Atlas (TCGA) and Gene Expression Profiling Interactive Analysis (GEPIA) data were employed to detect the TUBA1C mRNA expression and the relation between TUBA1C expression and ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
32
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 35 publications
5
32
0
Order By: Relevance
“…The researches exposed that microtubules combined with many microtubule-related proteins such as g α-, β-, and γ-tubulin aggregate to achieve various cellular functions in the cell cycle (mitosis and meiosis) [ 17 , 18 ]. Moreover, TUBA1C, a subtype of α-tubulin, which is composed of microtubule structure, was reported to be overexpressed and promotes oncogenesis in pancreatic ductal adenocarcinoma via Regulating the cell cycle [ 19 ]. In this study, we also found that cells transfected with SARS-COV-2 N protein usually had a higher TUBA1C expression.…”
Section: Discussionmentioning
confidence: 99%
“…The researches exposed that microtubules combined with many microtubule-related proteins such as g α-, β-, and γ-tubulin aggregate to achieve various cellular functions in the cell cycle (mitosis and meiosis) [ 17 , 18 ]. Moreover, TUBA1C, a subtype of α-tubulin, which is composed of microtubule structure, was reported to be overexpressed and promotes oncogenesis in pancreatic ductal adenocarcinoma via Regulating the cell cycle [ 19 ]. In this study, we also found that cells transfected with SARS-COV-2 N protein usually had a higher TUBA1C expression.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also reported that TUBA1C is associated with cell proliferation, and it also regulates cell cycle in many types of cancers. Furthermore, the expression of TUBA1C was reported to be correlated with p53 expression in pancreatic ductal adenocarcinoma [ 12 ]. Previous studies have reported that tubulin regulates cell metabolism and glucose stress response, reducing the dependence of cells on glycolysis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, α-tubulin is also associated with the development of astrocytoma and chemotherapeutic resistance of liver cancer [ 11 ]. Moreover, TUBA1C is a subtype of α-tubulin, and its overexpression is associated with the poor prognosis of hepatocellular carcinoma (HCC) and pancreatic ductal adenocarcinoma [ 12 , 13 ]. However, no previous study has elucidated how the overexpression of TUBA1C affects LUAD patients.…”
Section: Introductionmentioning
confidence: 99%
“…ST6GALNAC2 has functions in the PI3K/AKT pathway (Ren et al, 2014), which is involved in many cellular processes, including proliferation, differentiation, apoptosis, cell cycle progression, and cell motility (Bellacosa et al, 2005;Engelman et al, 2006). SLC25A4 has been implicated to have many transport functions for various molecules on the mitochondrial membrane, including ATP/ADP and amino acids, which are molecules constituting cellular energy sources (Albahde et al, 2020).…”
Section: Discussionmentioning
confidence: 99%